2018
DOI: 10.1007/s13555-018-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Water-Based Head Lice Lotion: A Randomized, Controlled, Investigator-Blinded, Comparative, Bicentric Study

Abstract: Introduction Silicones (e.g., dimethicone) are effective and safe alternatives to insecticides for the treatment of head lice. However, silicones are lipophilic substances and do not only leave the hair greasy but they are also difficult to wash out. We have evaluated the efficacy and safety of a potential solution to this problem: an aqueous dispersion of a novel silylated polyol that has the same mode of action as dimethicone (suffocation) without its negative impact on hair characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Nowadays, resistance-prone insecticide-based products for the treatment of pediculosis are gradually going to be replaced by alternative new preparations with a physical mode of action. These silicone-based products are both safe and clinically effective [10, 2022, 28, 29]. It is found in this study that dimeticone 4% is more efficacious in curing head lice infestations than either 1% permethrin or 0.2% d-phenothrin solutions using two interventions a week apart.…”
Section: Discussionmentioning
confidence: 88%
“…Nowadays, resistance-prone insecticide-based products for the treatment of pediculosis are gradually going to be replaced by alternative new preparations with a physical mode of action. These silicone-based products are both safe and clinically effective [10, 2022, 28, 29]. It is found in this study that dimeticone 4% is more efficacious in curing head lice infestations than either 1% permethrin or 0.2% d-phenothrin solutions using two interventions a week apart.…”
Section: Discussionmentioning
confidence: 88%
“…40 Many studies have reported the high efficacy and cure rates of DMT lotions applied twice, 7 days apart, for 8 hours or overnight. 30,41 In a randomized controlled trial, Burgess et al 42 reported that a single application of 4% dimethicone liquid gel for 15 minutes was more effective than two applications of 1% PER.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In the United Kingdom, the approximate equivalent cost per family member was €6.20-7.40 for DMT and €8.30-16.60 for treatment with PER. 41 In the United States, the cost of treating head lice was estimated at $365 million in 2004, with OTC products being less expensive than those available with a prescription. 50 However, this amount does not include the indirect costs of lice treatment, such as physician visits, purchase of lice combs, time spent removing nits/eggs from the scalps of infested individuals in institutions, and, most importantly, the cost of parental work absenteeism, especially where no-nit policies are implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of dimeticone has been shown in in vitro assays and randomized clinical trials, but it is not approved for use as a pediculicide by the FDA [44,45]. A class of water-based pediculicides that uses aqueous dispersions of silylated polyols shows promise in treating head lice and reducing the 'greasy' feeling in the hair that may remain after dimeticone use [46].…”
Section: Updates On Head Licementioning
confidence: 99%